Pautas para cuidadores - Suzanna Smith; Jennifer E. Gove (EDIS, 2009)
FCS2083Span, a 5-page fact sheet by Suzanna Smith and Jennifer E. Gove, is a new Spanish language version of FCS2083/HE018: Guidelines for Caregivers. It provides guidelines for managing stress, maintaining health, and getting the help that is needed to better enjoy all parts of one’s life. Includes references. Published by the UF Department of Family, Youth and Community Sciences, October 2009.